Paired Burst Stimulation Causes GABAA Receptor-Dependent Spike Firing Facilitation in CA1 of Rat Hippocampal Slices - Tominaga, Takashi; Tominaga, Yoko (Frontiers in Cellular Neuroscience, 2016)
The theta oscillation (4–8 Hz) is a pivotal form of oscillatory activity in the hippocampus that is intermittently concurrent with gamma (25–100 Hz) burst events. In in vitro preparation, a stimulation protocol that mimics the theta oscillation, theta burst stimulation (TBS), is used to induce long-term potentiation. Thus, TBS is thought to have a distinct role in the neural network of the hippocampal slice preparation. However, the mechanisms that make TBS uniquely induce such neural circuit modifications are still unknown. Using electrophysiology and voltage-sensitive dye imaging (VSDI), we have found that TBS induces augmentation of spike firing. The augmentation was apparent in the first couple of brief burst stimulation (100Hz four pulses) on a TBS-train in a presence of NMDA receptor blocker (APV 50 µM). In this study, we focused on the characterises of the NMDA independent augmentation caused by a pair of the brief burst stimulation (the first pair of the TBS; PBS). We found that PBS enhanced membrane potential responses on VSDI signal and intracellular recordings while it was absent in the current recording under whole-cell clamp condition. The enhancement of the response accompanied the augmentation of excitatory postsynaptic potential (EPSP) to spike firing (E-S) coupling. The paired burst facilitation (PBF) reached a plateau when the number of the first burst stimulation (priming burst) exceeds three. The interval between the bursts of 150 ms resulted in the maximum PBF. Gabazine (a GABAA receptor antagonist) abolished PBF. The threshold for spike generation of the postsynaptic cells measured with a current injection to cells was not lowered by the priming burst of PBS. These results indicate that PBS activates the GABAergic system to cause short-term E-S augmentation without raising postsynaptic excitability. We propose that a GABAergic system of area CA1 of the hippocampus produce the short-term E-S plasticity that could cause exaggerated spike-firing upon a theta-gamma activity distinctively, thus making the neural circuit of the CA1 act as a specific amplifier of the oscillation signal.